1994
DOI: 10.1111/j.1651-2227.1994.tb12992.x
|View full text |Cite
|
Sign up to set email alerts
|

Palpable lymph nodes of the neck in Swedish schoolchildren

Abstract: We studied 3592 Swedish schoolchildren, 8 or 9 years old, examined for palpable submandibular, cervical and supraclavicular lymph nodes. All children were skin tested with 2 TU PPD RT23 and with 0.1 microgram of Mycobacterium avium sensitin or 0.1 microgram of M. scrofulaceum sensitin. A total of 991 children had palpable lymph nodes in any of the three locations. Among them, 811 had lymph nodes in one location, 162 in two locations and 18 in three. In 312 children, the lymph nodes were > or = 5 mm in size in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 13 publications
(4 reference statements)
0
25
0
4
Order By: Relevance
“…Palpable lymph nodes may be found in the neck with a rate higher than 90% especially in children aged between 4 and 8 years (5). In another study, this rate was reported to be 38-45% in school aged healthy children (6). Although lymphadenomegaly is observed frequently especially in the childhood, it leads to concern in families and physicians because of the possibility of a malign disease.…”
Section: Discussionmentioning
confidence: 99%
“…Palpable lymph nodes may be found in the neck with a rate higher than 90% especially in children aged between 4 and 8 years (5). In another study, this rate was reported to be 38-45% in school aged healthy children (6). Although lymphadenomegaly is observed frequently especially in the childhood, it leads to concern in families and physicians because of the possibility of a malign disease.…”
Section: Discussionmentioning
confidence: 99%
“…Small lymph nodes are frequently palpable in health in the jugulodigastric area in adults and additionally in the posterior neck in young children. 38,39 There have been attempts to develop protocols for management of enlarged superficial nodes [14][15][16] but frequently the most important diagnostic tool is examination by an experienced clinician since suspicion of pathology is multifactorial and determined by size, form, consistency, site, associated symptoms and signs, and risk factors for disease. Following history taking and close examination of the area of nodal drainage and of other lymph node sites, performed by a clinician knowledgeable of locoregional disease processes, any suspicious node is subjected to fine needle aspiration cytology.…”
Section: Discussionmentioning
confidence: 99%
“…About 38% to 45% of otherwise normal children have palpable cervical lymph nodes [ 2 ]. Cervical lymphadenopathy is usually defi ned as cervical lymph nodal tissue measuring more than 1 cm in diameter [ 3 ].…”
Section: Introductionmentioning
confidence: 99%